2011
DOI: 10.1111/j.1365-2214.2011.01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and emotional understanding: a study on late‐adopted pre‐schoolers and their parents

Abstract: Adoption appears to be an intervention that assures the adoptive child an opportunity to catch up on emotional development and to partially resolve prior traumatic attachment experiences; adoptive parents play a central role in the emotional adjustment of their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 28 publications
7
51
1
1
Order By: Relevance
“…In a study on children with delayed adaptation to preschool, Barone and Lionetti (2011) achieved similar findings to our study and revealed that 25% of children developed secure attachment, 40% insecure attachment and 35% disorganized attachment. Green et al (2000) carried out a longitudinal study to evaluate attachment security of adolescents and reported that 29% of children had secure attachment style, 57% insecure and 14% disorganized attachment style.…”
Section: Resultssupporting
confidence: 88%
“…In a study on children with delayed adaptation to preschool, Barone and Lionetti (2011) achieved similar findings to our study and revealed that 25% of children developed secure attachment, 40% insecure attachment and 35% disorganized attachment. Green et al (2000) carried out a longitudinal study to evaluate attachment security of adolescents and reported that 29% of children had secure attachment style, 57% insecure and 14% disorganized attachment style.…”
Section: Resultssupporting
confidence: 88%
“…A further study on the same low-risk sample (Colle & Del Giudice, 2011;N ¼ 122) demonstrated associations between MCAST classifications and some features of emotional competence (emotion recognition and regulation skills). On a similar topic, Barone and Lionetti (2011) tested attachment representations against emotional competence in a small sample of late-adopted preschool children (N ¼ 20). Among the studies on higher risk samples, Futh, O'Connor, Matias, Green, and Scott (2008; N ¼ 113 early school-age children) found moderate to strong correlations between the MCAST engagement, positive content, coherence, and disorganization scales with maternal and teacher ratings of children's emotional and behavioral adjustment and their prosocial behavior.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Globally adoption research, on the one hand, has pointed out that late-adopted children are at high risk for elevated rates of socio-emotional and behavioural difficulties, including insecure/disorganized attachment patterns and internalizing and externalizing behaviour problems; on the other hand, high resilience, capacity of recovery from early deprivation, ability to build positive representations of new caregivers, and earned attachment security emerged in adopted children and their adoptive families (Barone & Lionetti, 2012;Bimmel, Juffer, van IJzendoorn, & Bakermans-Kranenburg, 2003;Pace & Zavattini, 2011;Pace, Cavanna, Velotti, & Zavattini, 2014;. Recent longitudinal attachmentbased studies on adoption and maternal sensitivity showed that more sensitive parenting -in infancy middle childhood, and/or adolescence-predicted continuity of secure attachment of adopted children from infancy to adolescence, less inhibited and delinquent behaviours in adolescence and secure attachment representations in young adulthood (Beijersbergen, Juffer, Bakermans-Kranenburg, & van IJzendoorn, 2012;Pace, Di Folco, Guerriero, Santona, & Terrone, 2015a;Schoenmaker et al, 2015a; IJzendoorn, 2013;van der Voort et al, 2014).…”
Section: Introductionmentioning
confidence: 99%